Pengaruh Capital Adequacy Ratio (CAR) Dan Financing To Deposit Ratio (FDR) Terhadap Return On Equity (ROE) PT BCA Syariah - Atmaja, Ardi; Rahmani, Nur Ahmadi Bi; Harahap, Rahmat Daim (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This research is motivated by the movement of the Capital Adequacy Ratio (CAR), which has fluctuated from year to year, in 2013, 2017, 2018, 2019 and 2020 towards Return On Equity (ROE), as well as the Financing to Deposit Ratio (FDR) also experienced fluctuating movements from year to year, in 2013, 2016, 2017 and 2019 in terms of Return On Equity (ROE), according to Irham Fahmi the higher the CAR, the stronger the bank's ability to bear the risk of any credit or productive assets , so the higher the CAR, the higher the Bank's Return On Equity (ROE) level and according to Lukman Dendawijaya, the higher the FDR Ratio, the Bank's profits will increase with the assumption that banks are able to channel financing effectively, with increasing bank profits, then Return On Equity ( ROE) will increase. This study aims to determine the effect of the Capital Adequacy Ratio (CAR) and the Financing to Deposit Ratio (FDR) on the Return On Equity (ROE) of PT Bank BCA Syariah. This research method uses a quantitative approach with secondary data sources, namely the financial balance sheet reports of PT Bank BCA Syariah Quarterly from 2013-2020. The analysis technique used is multiple linear regression test using the SPSS 25 tool. The results of this study indicate that the first H1 indicates that CAR has a significant effect on Return On Equity (ROE) with a negative value at PT BCA Syariah because t count is greater than t table t count value of 4.061 and t table 2.04523 with a significance profitability value of 0.000. Both H2 indicate that FDR has no significant effect on Return On Equity (ROE) at PT BCA Syariah because t count is smaller than t table, t count value is 0.203 and t table is 2.04523 with a significance profitability value of 0.840. The three H3s show that simultaneously CAR and FDR have an effect on ROE because F count (9.157) is greater than F table (3.33), then the value of the Coefficient of Determination (R2) shows that CAR and FDR have an effect of 38.7% on ROE and the remaining 61.3% are influenced by other variables.